Peran Pondok Hajjah Nuriyah Shabran Universitas Muhammadiyah Surakarta Dalam Pengembangan Kader Muhammadiyah Tahun 2016 - Arifin, Imam; , Dr. Abdullah Aly, M.Ag (2017)
Muhammadiyah is an Islamic movement or da'wah amar ma'rūf nahī munkar movement which is sourced to the Qur'an and Sunnah, and plays many roles in many areas of economic, social, religious and education. So it requires tough cadres' in order to realize the ideals of Muhammadiyah. Hajjah Nuriyah Shabran Boarding School of Muhammadiyah University of Surakarta is an institution with the purpose of forming the cadres to nurture, educate and develop potential cadres becaming scholars development, thinkers and organizers who master Islamic sciences, socio-cultural sciences, and theory and practice of management and leadership, da'wah, the development of ummah with appropriate experience and understanding of Muhammadiyah. The issues and the purpose of this research are roles of Hajjah Nuriyah Shabran Boarding School of Muhammadiyah University of Surakarta in developing cadres as well as supporting and inhibiting factors in developing the cadres of Muhammadiyah. This research uses qualitative method in which data are collected interviews, observations and documentation, and then analyzed by descriptive qualitative method. Based on the research, it can be concluded that the role of the Hajjah Nuriyah Shabran Boarding School of Muhammadiyah University of Surakarta in developing cadres' are the implementation of educational progam and curriculum, the construction of da'wah and full dedication to the study as well as the activities of library. The supporting factors of Hajjah Nuriyah Shabran Boarding School in developing cadre of Muhammadiyah are the existence of scholarship, adequate infrastructure, good selection and organized students' experience in the field of the organization. Meanwhile, the inhibiting factors in developing Muhammadiyah's cadre in Hajjah Nuriyah Shabran Boarding School are the different character of students based on the region, less synchronization of the schedule and the lack of human resources due to the large number of requests by the public devotion.